Peutz-Jeghers Syndrome: Diagnostic and Therapeutic Possibilities of Modern Intraluminal Endoscopy as Shown on Own Clinical Observations - M. M. Lokhmatov; T. N. Budkina; V. I. Oldakovsky; E. U. Diakonova (Union of pediatricians of Russia, 2016)
Peutz-Jeghers syndrome is a relatively rare autosomal-dominant inheritance type disease characterized by multiple hamartomas in the gastrointestinal tract. Treatment of such patients is traditionally surgical, but nowadays, due to the introduction of new methods of intraluminal endoscopy, it is often possible to avoid open abdominal operations, diagnose and remove the hamartomatous polyps in a minimally invasive way. The aim of this article is to demonstrate the diagnostic and surgical capabilities of modern intraluminal endoscopy for the treatment of patients with multiple hereditary gastrointestinal polyposis as shown on our own clinical observations. The technique of deep single balloon enteroscopy in conjunction with standard routine endoscopic manipulations allows to perform a total examination of the whole gastrointestinal tract and, if necessary, to remove almost all epithelial neoplasia, which certainly has a positive impact on the quality of the patient's life.